Fib model code for concrete structures 2010 (Ernst & Sohn, a Wiley brand, 2013)
The International Federation for Structural Concrete (fib) is a pre-normative organization. 'Pre-normative' implies pioneering work in codification. This work has now been realized with the fib Model Code 2010. The objectives of the fib Model Code 2010 are to serve as a basis for future codes for concrete structures, and present new developments with regard to concrete structures, structural materials and new ideas in order to achieve optimum behaviour. The fib Model Code 2010 is now the most comprehensive code on concrete structures, including their complete life cycle: con.